The Heme Metabolite Carbon Monoxide Facilitates KSHV Infection by Inhibiting TLR4 Signaling in Endothelial Cells - Botto, Sara; Gustin, Jean K.; Moses, Ashlee V. (Frontiers in Microbiology, 2017)
KSHV is the etiologic agent of Kaposi sarcoma (KS) and certain rare B cell lymphoproliferative disorders. KSHV infection of endothelial cells (EC) in vitro increases expression of the inducible host-encoded enzyme heme oxygenase-1 (HO-1), which is also strongly expressed in KS tumors. HO-1 catalyzes the rate-limiting step in the conversion of heme into iron, biliverdin and the gasotransmitter carbon monoxide (CO), all of which share anti-apoptotic, anti-inflammatory, pro-survival and tumorigenic activities. Our previous work has shown that HO-1 expression in KSHV-infected EC is characterized by a rapid yet transient induction at early times post-infection, followed by a sustained upregulation co-incident with establishment of viral latency. These two phases of expression are independently regulated, suggesting distinct roles for HO-1 in the virus life cycle. Here, we investigated the role of HO-1 during acute infection, prior to the onset of viral gene expression. The early infection phase involves a series of events that culminate in delivery of the viral genome to the nucleus. Primary infection also leads to activation of host innate immune effectors, including the pattern recognition receptor TLR4, to induce an antiviral response. It has been shown that TLR4-deficient EC are more susceptible to KSHV infection than wild-type controls, suggesting an important inhibitory role for TLR4 in the KSHV life cycle. TLR4 signaling is in turn subject to regulation by several virus-encoded immune evasion factors. In this report we identify HO-1 as a host protein co-opted by KSHV as part of a rapid immune evasion strategy. Specifically, we show that early HO-1 induction by KSHV results in increased levels of endogenous CO, which functions as a TLR4 signaling inhibitor. In addition, we show that CO-mediated inhibition of TLR4 signaling leads to reduced expression of TLR4-induced antiviral genes, thus dampening the host antiviral response and facilitating KSHV infection. Conversely, inhibition of HO-1 activity decreases intracellular CO, enhances the host antiviral response and inhibits KSHV infection. In conclusion, this study identifies HO-1 as a novel innate immune evasion factor in the context of KSHV infection and supports HO-1 inhibition as a viable therapeutic strategy for KS.